Is a Brief Online Booklet Sufficient to Reduce Fear of Cancer Recurrence or Progression in Women With Ovarian Cancer? - Pradhan, Poorva; Sharpe, Louise; Butow, Phyllis N.; Smith, Allan Ben; Russell, Hayley (Frontiers in Psychology, 2021)
Background: Fear of cancer recurrence or progression (FCR/P) is a common challenge experienced by people living with and beyond cancer and is frequently endorsed as the highest unmet psychosocial need amongst survivors. This has prompted many cancer organizations to develop self-help resources for survivors to better manage these fears through psychoeducation, but little is known about whether they help reduce FCR/P. Method: We recruited 62 women with ovarian cancer. Women reported on their medical history and demographic characteristics and completed the Fear of Progression Questionnaire-Short Form (FoP-Q-SF). They then read a booklet on FCR specifically created for Ovarian Cancer Australia by two of the authors (ABS and PB). One week after reading the pamphlet, 50/62 women (81%) completed the FoP-Q-SF and answered questions about their satisfaction with the booklet. Results: More than half of the women (35/62; 56.5%) scored in the clinical range for FCR/P at baseline. Of the completers, 93% said that they would recommend the pamphlet to other women. Satisfaction with the pamphlet was relatively high (75.3/100) and more than two-thirds of women rated it as moderately helpful or better. However, FCR/P did not change significantly over the week following reading the booklet (t (49) = 1.71, p = 0.09). There was also no difference in change in FCR/P between women in the clinical versus non-clinical range on the FoP-Q. Women high in FCR/P rated the booklet as less helpful in managing FCR/P (r = -0.316, p = 0.03), but overall satisfaction with the booklet was not associated with degree of FCR/P (r= -.24, p= .10). Conclusions: These results suggest that a simple online FCR booklet is acceptable to women with ovarian cancer and they are satisfied with the booklet, but, it was insufficient to change in FCR/P levels. These results suggest that such resources are valued by women with ovarian cancer, but more potent interventions are necessary to reduce FCR in this population. Keywords: Cancer, Oncology, neoplasms, Fear of cancer recurrence, Fear of cancer progression, ovarian cancer.